ANALISIS PENDAPAT PUBLIK TERHADAP PUBLIC FIGURE DENGAN MENGGUNAKAN METODE NAIVE BAYES - Mansur, Januar; Mawardi, Viny Christanti; Sutrisno, Tri (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
Public Figure is a talented idol figure. For example, such as sportsmen, music players or film actors. Because it is the focus of the community, the behavior of a public figure is interesting to comment on. This is supported by the use of social media by Indonesian people such as Twitter. On the public figure page, existing comments can be analyzed to find out the sentiments of the people who are classified as positive, negative, and neutral. For a small amount of data, the comment classification process can be done manually, but if the data is too much it requires a system equipped with classification methods, so classification can be done quickly. The application of this classification will use a diagram feature, when the user types the public figure name the desired one will output the classification with a diagram. In determining the classification results will use the Naïve Bayes classification method. This application uses 6 training data classes of 2104 data with results of the system produced an accuracy of 96.47% and 6 trainng data balance of classes of 750 data with the result of the system produced an accuracy of 87.97%.